Impact of cadmium exposure on swine enterocytes. (1st May 2018) - Razzuoli, E.; Mignone, G.; Lazzara, F.; Vencia, W.; Ferraris, M.; Masiello, L.; Vivaldi, B.; Ferrari, A.; Bozzetta, E.; Amadori, M.
Highlights: IPEC-J2 cells are suited to mimic interactions between host and Cadmium. IPEC-J2 cells can uptake Cadmium. Low and moderate Cadmium concentration perform different effects. Cadmium performs pro-inflammatory effects and reduction of cell viability. Abstract: We tested cadmium (Cd2+) effects on porcine IPEC-J2 cells, which represent an in vitro model of the interaction between intestinal cells and both infectious and non-infectious stressors. Accordingly, we investigated the effects of low (2 μM) to moderate (20 μM) concentrations of Cd2+, in terms of pro-inflammatory gene expression and protein release, as well as of infectivity in a Salmonella typhimurium penetration model. Our data showed a significant (P < .001) increase of intracellular Cd2+ after 3, 6 and 24 h of exposure with respect to levels at 1 h. These data showed the ability of IPEC-J2 to absorb Cd2+ as a function of both time and concentration. Also, the absorption of this heavy metal was related to a significant modulation of important pro-inflammatory messengers. In particular, down-regulation of IL-8 was associated with a significant decrease of Salmonella typhimurium ability to penetrate into IPEC-J2 cells, in agreement with a previous study in which an anti-IL 8 antibody could significantly inhibit Salmonella penetration into the same cells (Razzuoli et al., 2017 ). This finding demonstrates the ability of Cd2+ to affect the outcome of an important host-pathogen relationship. In conclusion, our study highlighted the ability of an environmental pollutant like Cd2+ to modulate innate immune responses in terms of chemokine release and gene expression, and susceptibility to microbial infections.